ECONOMIC, POLITICAL, AND CIVIL SOCIETIES AT PEMUTERAN VILLAGE, BALI IN COASTAL AND MARINE ENVIRONMENTAL PRESERVATION - Mudana, I Wayan (E-Journal of Cultural Studies; Volume 6, Number 1, May 2013)
This study was focused on questions (1) what factors caused the economic, political, and civil societies to invest their social capital in the preservation of marine and coastal environments at Pemuteran Village? (2) What was the social capital invested by the economic, political, and civil societies in the preservation of coastal and marine environments at Pemuteran Village like? (3) What was done to discipline the maintenance of the social capital invested in the preservation of the coastal and marine environments at Pemuteran Village? Some critical theories were used to analyze the answers to the problems. Qualitative research method with the approach of cultural studies was employed in this study. The data were collected through observation, in-depth interview, and library research. The data were qualitatively and descriptively analyzed. The result of the study showed that the cooperation among the economic, political, and civil societies to invest their social capital in the preservation of the marine and coastal environments at Pemuteran Village was based on the awareness of the condition of the natural environment, ecological smartness, meaningfulness which was economic, political, sociological, and socio-religious in nature, and developmental policy. The social capital invested by the economic, political and civil societies was in the forms of the ideologies of tri hita karana, nyegara-gunung, menyama braya, kinship system, neighborhood relation, traditional village, and administrative village. It was maintained through cultural socialization process, and physical and spiritual disciplining process.
Keywords: economic, political, and civil societies, social capital, preservation of marine and coastal environment.